2018
DOI: 10.1099/jgv.0.001057
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) 16 E6 oncoprotein targets the Toll-like receptor pathway

Abstract: Cervical cancer is one of the leading causes of death in women worldwide and is etiologically linked to human papillomavirus (HPV) infection. Viral early proteins E6 and E7 manipulate cellular functions to promote the virus life cycle and are essential to the cellular transformation process. The innate immune system plays a pivotal role in the natural history of HPV infection. Among the various proteins that mediate the innate immune response, Toll-like receptors (TLRs) recognize pathogen-associated molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In this study we identify IKKβ as a mediator of the HPV 18 E6 and hUBE3A-induced cellular defects in both fly and human cancer models. This is consistent with previous studies demonstrating that HPV 16 E6 interacts with components of the innate immune pathway, including IKKβ, and it activates the NF-κB transcription factor 52,53 . The role of the innate immune system in HPV infection and cancer progression is not well understood.…”
Section: Discussionsupporting
confidence: 93%
“…In this study we identify IKKβ as a mediator of the HPV 18 E6 and hUBE3A-induced cellular defects in both fly and human cancer models. This is consistent with previous studies demonstrating that HPV 16 E6 interacts with components of the innate immune pathway, including IKKβ, and it activates the NF-κB transcription factor 52,53 . The role of the innate immune system in HPV infection and cancer progression is not well understood.…”
Section: Discussionsupporting
confidence: 93%
“…This diversity could be related to the phylogenetic associations between different HPV species or with the interaction of different oncoproteins (E6, E7) with proteins involved in apoptosis (it has been reported that different genotypes differentially increase myc expression [51] [52]) or E6, which can suppress the transcription of TLR9 [53] or genes involved in interferon signaling (STAT), producing an inactivation state of the immune system and the inflammatory response associated to the presence of the viral infection [54].…”
Section: Discussionmentioning
confidence: 99%
“…The HPV16 E6 prepared in this study might have promoted NF-kB activation by upregulating MyD88 and TRAF6, whereas Caski cells might have inhibited NF-kB signaling via the E7 protein. Hence, the activation of NF-kB pathway and the expression of MyD88 and TRAF6 proteins were affected by HPV-positive cells at different infection stages [12].…”
Section: Discussionmentioning
confidence: 97%